2011
DOI: 10.1111/j.1745-4514.2011.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF VARIETAL AND pH VARIATION ON ANTIHYPERGLYCEMIA AND ANTIHYPERTENSION PROPERTIES OF LONG-TERM STORED APPLES USING IN VITRO ASSAY MODELS

Abstract: This study provides further in vitro evidence for inhibition by apple extracts of alpha‐glucosidase and alpha‐amylase for potential antihyperglycemia benefits and angiotensin converting enzyme inhibitory activity for associated antihypertension potential. This was investigated in peel and pulp aqueous and ethanol extracts from 10 different long‐term stored apple cultivars. “Red Delicious” and “Cortland” cultivars had significantly higher total phenolic content and inhibitory antioxidant capacity, with high cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 42 publications
3
11
1
Order By: Relevance
“…(2010) found that apple peel had higher antioxidant capacity, total phenolic content, alpha‐glucosidase inhibitory activity than pulp, while apple pulp had high alpha‐amylase inhibitory activity. Similar results were observed for long‐term stored apples (Barbosa et al . 2011).…”
Section: Introductionsupporting
confidence: 89%
See 2 more Smart Citations
“…(2010) found that apple peel had higher antioxidant capacity, total phenolic content, alpha‐glucosidase inhibitory activity than pulp, while apple pulp had high alpha‐amylase inhibitory activity. Similar results were observed for long‐term stored apples (Barbosa et al . 2011).…”
Section: Introductionsupporting
confidence: 89%
“…Both aqueous and ethanolic pulp extracts had low antioxidant capacity (8–29%) when compared with peel extracts. Barbosa et al . 2010, 2011 found similar range for DPPH radical inhibition‐based antioxidant activity and total phenolic content for the apple varieties studied.…”
Section: Results and Discusssionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have reported the inhibitory potentials of starch hydrolysing enzymes in a number of plants such as pea nut (Arachis hypogaea) (Irshad and Sharma 1981), cowpea (Piergiovanni and Gatta 1994), lima beans (Phaseolus lunatus) (Johnson et al 2013), white beans (Phaseolus vulgaris) (Barrett and Udani 2011), sorghum (Mulimani and Supriya 1993) and wheat (Heidari et al 2005). According to other reports, blackcurrant, blueberry (McDougall et al 2005), strawberry (Pinto et al 2008), apples (Barbosa and Pinto 2012) and ginger (Oboh et al 2010) also have the ability to inhibit the activity of a-glucosidase. According to other reports, blackcurrant, blueberry (McDougall et al 2005), strawberry (Pinto et al 2008), apples (Barbosa and Pinto 2012) and ginger (Oboh et al 2010) also have the ability to inhibit the activity of a-glucosidase.…”
Section: Introductionmentioning
confidence: 95%
“…Inhibitory potential of starch hydrolysing enzymes have also been detected in fruits and vegetables such as raspberry (Boath et al 2012), red grape (Mccue et al 2005), green pepper (Mccue et al 2005), cambucci and cupuacu fruits (Pinto et al 2008) and carrots (Mccue et al 2005). According to other reports, blackcurrant, blueberry (McDougall et al 2005), strawberry (Pinto et al 2008), apples (Barbosa and Pinto 2012) and ginger (Oboh et al 2010) also have the ability to inhibit the activity of a-glucosidase.…”
Section: Introductionmentioning
confidence: 97%